State Bar of California Annual Meeting Held at Century Plaza Hotel - Watkins, Howard::::::::: (1987)
Panel with Alvin Goldstein on far left; Robert Aitken at lectern, State Bar President Anthony Murray and attorney James Brosnahan seated